Terapia interdisciplinar no controle da obesidade: aspectos nutricionais, inflamação e controle neuroendócrino - Poli, Vanessa Fadanelli Schoenardie [UNIFESP] (2017)
Introduction: Obesity is a chronic disease and a huge public health problem worldwide. Adipose tissue is recognized as an endocrine organ producing adipokines, and its excess is associated with low-grade inflammatory processes that increase the risk of developing comorbidities. In addition to this inflammatory state, another important pathophysiological mechanism of obesity is the dysregulation of the neuroendocrine control of food intake. The etiology of obesity is multifactorial, with lifestyle factors such as inadequate diet and sedentary lifestyle being the most important. Interdisciplinary therapy for lifestyle changes is a treatment strategy that has been studied in recent years. Objective: To evaluate the impact of an interdisciplinary lifestyle modification therapy on the dietary pattern, inflammatory markers, neuropeptides and predictive equations of the resting energy expenditure (REE) in obese adults. Methods: Obese subjects (BMI: 30 to 39.9 kg/m2) with 30 to 50 years were submitted to an interdisciplinary therapy program during the course of one year. The therapy consisted of nutritional, psychological, physiotherapeutic and physical exercise interventions. Anthropometric evaluations of body composition (DXA) and blood collection (analysis of inflammatory markers and neuropeptides) were performed. REE was measured by indirect calorimetry. The 3- day food record was applied to evaluate food intake. The description of the food pattern was performed by the NOVA classification and Diet Quality Index (DQIDFG). All evaluations were performed at baseline and after therapy. The data were statistically analyzed and the level of significance was set at p<0.05. Results: In this study, 87 individuals were included, of whom 52 completed the therapy. The therapy program showed significant reduction of body mass (-6.7%), fat mass (- 5.5%), waist circumference (-5.8%) and serum leptin levels (-24.1%), IL-6 (-45.3%) and TNF-α (-17.3%), and significant increase of α-MSH (22.8%). Assessment of food consumption showed a significant reduction in macronutrient intake and consumption of ultra-processed foods (-4.6%); and an increase in DQI-DFG (21.3%) after therapy. Correlations were observed between the Δ consumption of UPFs and TNF-α (r=0.36; p=0.03); DQI-DFG and NPY (r=-0.42; p=0.009), and α-MSH (r=0.45; p=0.008). Multiple linear regression analysis showed that α-MSH was independently associated with diet quality index (β=0.015, P=0.008), and NPY inversely associated with diet quality index (β=-0.005, P=0.039). Agreement analysis between predictive equations and indirect calorimetry showed a great variation between the methods for the determination of REE. The Harris-Benedict and FAO/WHO/UNU equations showed bias <5% and were not significantly different from indirect calorimetry before and after interdisciplinary therapy. However, the Bland-Altman plots did not show a good agreement between the methods. Conclusion: The proposed interdisciplinary therapy program is an effective strategy in reducing anthropometric measures and in improving body composition, inflammatory profile and neuroendocrine control of food intake of obese adults. In addition, the therapy promoted positive qualitative changes in the food pattern according to the classification by the degree of food processing and diet quality index. Regarding the predictive equations for calculating energy requirements, they should be used with caution in clinical practice.